Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Loyalitas Pelanggan Coffee Shop Tebing Senja.Id - Azura, Putri Aprilia; Cholid, Idam (MDP Student Conference, 2024)
The purpose of this research is to analyze service quality and trust that influence customer loyalty at the Tebing Senja.id coffee shop as well as service quality and trust that influence customer loyalty at the Tebing Senja.id coffee shop. Data collection for this research distributed questionnaires to 216 respondents. Sampling used nonprobability sampling with a purposive sampling method with the help of SPSS 25. Partial test results show that service quality and trust have a significant positive effect on customer loyalty with a value of 0.00 < 0.05. The simultaneous test proves that the F value is 118,098 with a significant value of 0,000, which means that the variables of service quality and trust can be said to have a positive and significant effect on customer loyalty.